EFEKTIFITAS MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA PASKA OPERASI APENDIKTOMI - Nanda Masraini Daulay; Febrina Angraini Simamora (Jurnal Education and Development, 2019)
The Effectiveness including factors that can affect the healing process of wounds after appendectomy. The Early mobilization can facilitate blood circulation so that it can speed up the wound healing process. The purpose of this study is to know The Effectiveness of Early Mobilization to Wound healing of Post Surgery Appendectomy. The researcher conducted research at general hospital of padangsidimpuan city. This type of research is quantitative with a quasi experiment design. The sample in this study were 15 respondents. The Observation of wound healing was carried out on the REEDA scale. The results of observation of wound healing obtained mean on pretest is 6,5 with standard deviation 4,8 while a post-test mean is 5,5 with standard deviation 2,3. Data analysis using Shapiro-Wilk test to get dat not normally distributed, therefor for carry out a test on the effectiveness of wound healing with Wilcoxon test. With Wilcoxon test obtained value sig. 0,005 < 0,05 so that Ha accepted dan Ho rejected, the meaning that early mobilization is effectively applied to speed up the wound healing process in patients after appendectomy. Therefore the Early mobilization is good after 6 - 8 hours after appendectomy so that wound healing works well.